Perancangan dan Implementasi Sistem Monitoring Jaringan di MA Darut Taqwa Berbasis Web yang Mengintegrasikan dengan API MikroTik - Nurus Sobah; Muhammad Faishol Amrulloh (Puslitbang Sinergis Asa Professional, 2023)
MA Darut Taqwa is a school located in Pasuruan Regency, which has implemented a centralized internet network with large bandwidth. The high number of users accessing the network at MA Darut Taqwa requires a real-time monitoring system to ensure the quality and condition of the network on MikroTik. However, this school has not fully used real-time network management, so it requires a user monitoring system using the MikroTik API which is integrated through PHP and MySQL-based websites. This will be very useful for administrators in monitoring the network effectively. The implementation of the proposed system is the development of a PHP-based website that interacts with MikroTik devices via the API. Real-time monitoring is obtained by continuously querying and updating data, as well as providing administrators with up-to-date information about network usage. The results of this study show that the website application functions properly with the results that the website can provide real-time internet speed information on the proxy interface and can manage hotspots and Point-to-Point Protocol (PPP).